The Interplay of Personal Selling and Direct Marketing: An Exploratory Study in the Pharmaceutical Industry - Ann-Kristin Hansen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
Beyond dispute, personal selling represents the dominant and most effective promotional element in industrial settings, but its costs are quite substantial. Against this background, sales managers are forced to reexamine alternative approaches for servicing and informing customers in order to justify the productivity of their industrial selling mix. In this context, the complementary use of direct marketing to field selling becomes a primary concern as it allows for confidentiality and personalization of the message in contrast to mass communication while it provides information at a lower cost than does personal selling. However, no study has empirically investigated the interplay of personal selling and various direct marketing instruments with regard to several contextual factors determining the preferred use of direct marketing over personal selling so far. Thus, focusing on business-to-business transactions, this study's objective is to deepen the understanding of the direct marketing and personal selling interplay. Due to limited empirical insights to this area, an exploratory research design is adapted. Results indicate that the advantageousness of direct marketing in comparison to personal selling is determined by customer-related, internal and external contextual conditions. Further, a well-designed interplay helps to improve selling productivity, brand awareness and customer satisfaction – and thus business unit performance.
Keywords: 650